The Effect of Classroom Learning Media and Zoom Meeting on Student Motivation through Lecturer-Student Interaction (Case Study of 2023-2024 Batch Students) - Cherry Pramudhita Artanti; Indah Nurlitasari; Osly Usman (International Conference on Digital Business Innovation and Technology Management (ICONBIT), 2025)
This study aims to analyse the effect of classroom learning and learning through Zoom Meeting on student learning motivation, with lecturer-student interaction as a mediating variable. The method used is a quantitative approach with Partial Least Square Structural Equation Modeling (PLS-SEM) analysis technique using SmartPLS 4.0 application. The research sample consisted of 102 students from various universities. The results showed that classroom learning has a significant direct effect on students’ learning motivation. In contrast, learning through Zoom does not have a direct effect, but has an indirect effect through lecturer-student interaction. Lecturer-student interaction proved to be a significant mediator in increasing learning motivation. Thus, the quality of interaction between lecturers and students is an important factor in the success of the learning process, both online and offline.